A dynamic task assignment approach based on individual worklists for minimizing the cycle time of business processes. (September 2016) - Xie, Yi; Chien, Chen-Fu; Tang, Ren-Zhong
Highlights: A dynamic task assignment approach is developed for minimizing the cycle time of business processes. This approach is easier to achieve global optimization and control the resources performing tasks in details. This approach can adapt to the dynamic execution of business processes and bring a better performance in cycle time. The validity and practical viability of this approach has been verified in simulation experiments and practical applications. Abstract: To improve business process performances, this study develops a dynamic task assignment approach for minimizing the cycle time of business processes. In particular, considering the quantity of each resource as a new parameter, a formal business process model and a novel approach to estimating the mean cycle time of activities are presented for task assignment based on individual worklists, queuing theory and stochastic theory. Then the mathematical model of task assignment and its solution for minimizing the cycle time are proposed, and the dynamic task re-assignment policy is developed to further reduce the cycle time. The results of simulation experiments and practical applications show our approach has better validity and practical viability than other approaches.